Research on the interference control and resource allocation in D2D communication - Kangkang FAN; Ying DONG; Zhihong Qian; Xue WANG (Tongxin xuebao)
In order to solve the problem of interference caused by D2D users reuse cellular resources in cellular network,an algorithm of interference control and resource allocation of D2D communication in single cell cellular system was proposed.Firstly,an interference graph was constructed according to the interference between users in the system to find the reusable channel resource for D2D users.Then,the channel resource pre-allocation and the channel switching policy were performed for D2D users in sequence according to the preset D2D user priority.The simulation results show that the proposed algorithm can significantly improve the system throughput and the access rate of D2D users so that the system can achieve better performance in the presence of small or large number of D2D users.